Innovation - the role of trust - Lazányi, Kornélia (Serbian Journal of Management, 2017)
Innovations and constant change are inevitable parts of our everyday lives. It is not only because advanced technologies are more effective, but mostly because in the 21st century more and more realise that scarce resources – among them the safe and clean environment as such - necessitate a paradigm change and intense innovation. This revolution is easily trackable in the organisational and (supra)national policies. However, innovation, and its necessary prerequisites are seldom investigated from the individuals’ point of view.It is easy to understand that inter-organisational trust is inevitable on both the consumers’ and the providers’ (innovators’) side, however, it has to be made clear that an innovative organisation has to create a trusting environment within the company, in order to foster collaboration, the generation of new ideas, creativity and finally innovation.The present paper endeavours to call attention to the notion of trust and its antecedents and consequences in relation to innovations. The aim is to provide assistance in understanding how to develop trust in each other and hence foster further innovations and development.